Eras in epidemiology the evolution of ideas - Susser, Mervyn; Stein, Zena. (New York ; Oxford : Oxford University Press, 2009)
The authors trace the evolution of epidemiological ideas from earliest times to the present, starting with the early concepts of magic and the humours of Hippocrates and moving through the dawn of observational methods, the Enlightenment and the French Revolution up to the development of eco-epidemiology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epidemiology -- History